CURRENT APPROACHES TO THE DIAGNOSIS OF CERVICAL DISEASE IN PREGNANT - E. S. Sverdlova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The purpose of the article is to determine the factors contributing to the development of cervical intraepithelial neoplasia and cervical cancer during pregnancy, and the assessment of the impact of HIV infection on the progression of dysplasia of the cervix during pregnancy. 1146 pregnant women at various stages of gestation, including in 124 HIV-positive were examined. The control group included 146 pregnant women without HIV The survey included: examination, colposcopy, PAP test, PCR for HPV and Chlamydia, HlV diagnosis activity: ELISA, immune blotting, PCR, VIRAL LOAD, identification numbers of CD4 + and CD8 +. The presence of HPV in HIV-positive pregnant women is the leading risk factor for cervical dysplasia epithelium regardless of gestational age. Dysplasia may be suspected at colposcopy examination. The final diagnosis is stated morphologically. HIV in combination with CIN detected in the early stage of pregnancy, it is important to determine the risk of cervical cancer, while maintaining the pregnancy. You must assign the ART in detecting cervical intraepithelial neoplasia of 2-3 grade. When CIN 3 during pregnancy is appropriate elective caesarean section, as a way to prevent the development of cervical cancer after the birth, along with a reduced likelihood of intrapartum transmission of HIV.